Heaven sent rain [large type] : a novel - Snelling, Lauraine (Center Point Large Print, 2014)
Dinah Taylor has an orderly life that is just how she likes it. A perfectly furnished luxury apartment, a satisfying career as a scientist and CEO of her own company, and an uncomplicated personal life. But all of that changes when she meets seven-year-old Jonah.